Digital velocity profile estimator of blood flow in the heart and large blood vessels - KARŁOWICZ, P.; LIWSKI, J.; PIECHOCKI, M.; SECOMSKI, W.; NOWICKI, A. (Archives of Acoustics, 1990)
The paper discusses principles of a digital multigate system for Doppler frequency measurements. The conception of a system with serial data processing, based on the Doppler frequency measurement with the "zero crossing" method, is described. Problems with the recognition of the direction of flow in the digital system are presented, as well as two solutions, tested in practice, which limit occurring measuring errors. An example of an actual flow measurement made with the application of a model of the presented device is described, and possible errors resulting from the "zero crossing" technique are given. In order to improve properties of the system the use of a digital low-pass filter is proposed. The conception of such a filter is described.